2021
DOI: 10.1038/s41598-021-95075-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological and environmental influences on motor coordination in Peruvian children and adolescents

Abstract: This study investigated the associations between biological and environmental factors and gross-motor coordination (GMC) in Peruvian children and adolescents. The sample comprised 7401 boys and girls, aged 6–14 years, recruited from three geographical regions: sea-level, Amazon and high-altitude. Biological variables included age, sex, height, BMI, physical fitness, stunting, and maturational status. Environmental influences included geographical region and school characteristics. Gross-motor coordination was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
2
7
0
1
Order By: Relevance
“…Children living at higher altitudes have higher lung function relative to children living at lower altitudes [ 91 , 92 , 93 ]. Studies have shown that after a period of acclimatization to the plateau, students’ CRF improved significantly, and adolescents living at relatively high altitudes had better motor coordination, which also corroborates our findings that the appropriate altitude is beneficial to adolescents’ physical performance [ 94 , 95 ]. The spatial pattern of the influence of altitude may be explained by the fact that although youth physical fitness failure rates are influenced by a combination of factors, they are currently largely dependent on socio-economic development conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Children living at higher altitudes have higher lung function relative to children living at lower altitudes [ 91 , 92 , 93 ]. Studies have shown that after a period of acclimatization to the plateau, students’ CRF improved significantly, and adolescents living at relatively high altitudes had better motor coordination, which also corroborates our findings that the appropriate altitude is beneficial to adolescents’ physical performance [ 94 , 95 ]. The spatial pattern of the influence of altitude may be explained by the fact that although youth physical fitness failure rates are influenced by a combination of factors, they are currently largely dependent on socio-economic development conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Longitudinal studies should identify the direction of these effects. Previous research suggests that children's weight status negatively influences future levels of some aspects of motor competence and vice versa (Pereira et al 2021). Therefore, preventive measures such as education, motivation for PA and observation of children's weight status and motor competence levels are crucial.…”
Section: Predictors Of Basic Motor Competenciesmentioning
confidence: 99%
“…Regarding parental education as a sub domain of socio-economic status, other studies used a more systematic approach to assess this multi-facetted construct, e.g., Klein et al [29]. Additionally, other authors have stressed the role of other factors, such as children's biological characteristics, on the determination of PF [43]. Regarding PA, future studies might consider using already validated questionnaires to assess PA levels, e.g., the International Physical Activity Questionnaire (IPAQ) [44].…”
Section: Limitations and Strengthsmentioning
confidence: 99%